Cultura Organizacional em instituições de ensino superior: do foco no cidadão ao cumprimento das normas - Carvalho, Renata Albuquerquer de (2019)
Assuming the coexistence of bureaucratic and managerial management models in the daily life of public universities, this work intends to explore, through the perception of public servants and in light of organizational culture, the administrative practices of the Pro-Rectories of a University, when it comes to its adherence to rules and its focus on the citizen. That is, the study aims at observing the valorization (or devaluation) of formality, impersonality, hierarchy and the focus on users' needs, as it seeks to understand how the compliance of the servers with such elements could influence the practices of public organizations toward the achievement of their main objective: social welfare. The methodological procedures of the dissertation included, besides bibliographical research, interviews with servers of the studied institution, which consisted of an exploratory case study. It was possible to observe the attachment of the interviewed subjects to the characteristics of the bureaucracy, especially the formalism and impersonality. The study shows that the bureaucracy, through its written rules, acts as a tool to protect the servers against a general distrust of their own practices. Furthermore, it became possible to understand that the servants of the studied University direct their practices much more to the compliance of standards and rules than to the focus in the needs of its services’ users